Objetividade na Investigação Social: uma discussão entre pragmatismo e empirismo lógico - Cunha, Ivan Ferreira da (Cognitio: Revista de Filosofia, 2022)
Otto Neurath and John Dewey share the understanding that science must have a prominent role in democratic social reform. This is a common aim that brought logical empiricism and pragmatism together in the first half of the 20th century, but there are differences between the two stances. On the one hand, Neurath sees a limitation of scientific knowledge, considering that it cannot determine decisions to be taken in the course of social reform. Such decisions, in the logical empiricist view, are a matter of politics. On the other hand, Dewey sees a continuity among all forms of inquiry and, therefore, the conclusions of valuational inquiry are analogous in their epistemic claims to the conclusions in factual (natural or social inquiry). This paper investigates the divergence and concludes that pragmatist continuity of inquiry is set in a psychological context that disregards a difference in objectivity between factual and valuational inquiry.